Phenolic profile, antioxidant and antimicrobial activity of Echinophora tenuifolia L. subsp. sibthorpiana - Stanislav Dyankov; Stanislava Ivanova; Kalin Ivanov; Iva Slavova; Neli Ermenlieva; Emilia Georgieva; Maria Bozhkova; Sylvia Stamova (Pharmacia)
In the present study, the phenolic profile, the antioxidant activity, and the antimicrobial activity of an aqueous-methanolic extract prepared from the aerial parts of Echinophora tenuifolia subsp. sibthorpiana growing in Bulgaria were investigated for the first time. The evaluation of the phenolic composition of the extract revealed high levels of total phenols (111.3 ± 9.1 mg GAE/g dry extract) and the presence of the phenolic acids chlorogenic acid, p-coumaric acid, ferulic acid, salicylic acid, rosmarinic acid, the flavonol glycoside rutin, and the flavanone glycoside hesperidin. The highest concentration was observed for rutin (29.625 mg/g). The extract demonstrated good radical scavenging activity in the DPPH assay (IC50 71.3 ± 0.01 μg/mL) and antioxidant capacity in the ferric-ferrozine assay (405.1 ± 39.9 μmol/g). In addition, the extract exhibited antibacterial activity against E. coli (MIC 1.85 mg/mL, MBC 3.5 mg/mL) and S. aureus (MIC 3.7 mg/mL). In contrast, no antifungal activity against C. albicans was observed.